Réflexions sur la notion de conversion dans la diffusion du bouddhisme theravāda au Népal - Letizia, Chiara (Anthropologica, 2022)
Beginning in the 1920s in Nepal, Theravada Buddhism was adopted by the Newars who were attracted to its novel approach. Recently, this movement has spread to other Hinduized ethnic groups. The confrontation between local traditions and this modern form of Buddhism leads us to question the applicability of the idea of conversion in the Nepalese context. In traditional Nepal, religion is the principle that structures society and conversion is not possible and is even constitutionally prohibited. It seems to become relevant, however, when traditional religion generalizes its message beyond the social contexts for which it is intended as is the case of the diffusion of Buddhist modernism in contemporary Nepal.